Design of low power SRAM- based ubiquitous sensor for wireless body area networks. Issue 5 (18th November 2021) - Neeraj, Kumar; Mahaboob Basha, Mohammed; Gundala, Srinivasulu
Abstract : Purpose: Smart ubiquitous sensors have been deployed in wireless body area networks to improve digital health-care services. As the requirement for computing power has drastically increased in recent years, the design of low power static RAM-based ubiquitous sensors is highly required for wireless body area networks. However, SRAM cells are increasingly susceptible to soft errors due to short supply voltage. The main purpose of this paper is to design a low power SRAM- based ubiquitous sensor for healthcare applications. Design/methodology/approach: In this work, bias temperature instabilities are identified as significant issues in SRAM design. A level shifter circuit is proposed to get rid of soft errors and bias temperature instability problems. Findings: Bias Temperature Instabilities are focused on in recent SRAM design for minimizing degradation. When compared to the existing SRAM design, the proposed FinFET-based SRAM obtains better results in terms of latency, power and static noise margin. Body area networks in biomedical applications demand low power ubiquitous sensors to improve battery life. The proposed low power SRAM-based ubiquitous sensors are found to be suitable for portable health-care devices. Originality/value: In wireless body area networks, the design of low power SRAM-based ubiquitous sensors are highly essential. This design is power efficient and it overcomes the effect of bias temperature instability.